Developing grammar teaching approach based on X-bar theory - Saeipoor, Neda (2011)
The availability of X-bar theory to adult second language learners has been discussed since the 1990s. This study attempted to investigate the effectiveness of presenting X-bar parameters in their order of availability in the X-bar tree hierarchy. The research was conducted to study the possible effects of presenting the syntax rules to the participants following the order of the X-bar parameters’ availability and triggering the target language parameter resetting by emphasizing on the input. The major objective of this research was to devise and apply an approach for teaching English grammar based on the X-bar theory and to test the efficiency of this approach on improving English grammar proficiency and general language proficiency in UPM non-TESL students speaking Farsi as their first language. This study was based on a mixed method design to develop and test the efficiency of a teaching approach for facilitating syntax acquisition in adult second language learners. It was assumed that the use of both quantitative and qualitative methods,in combination, would provide a better understanding of the research problem and questions. The research was conducted through a course of 20 sessions attended by 25 participants chosen based on the results of the Oxford Placement Test to ensure homogeneous grammar proficiency. Teaching methods, practices and course content were developed during the course by considering the participants’responses with regard to syntax awareness, interests and progress. Each session’s content and activities were chosen based on the previous sessions' qualitative data analysis. The efficiency of this approach was assessed both through quantitative tests (Pretest, Post-test and two grammar tests conducted during the course) and qualitative analysis (following the participants progress during the course based on the class observations, field notes and interview). Both quantitative and qualitative assessments indicated significantly positive improvement in the participants’ general language proficiency and English grammar proficiency. It can be concluded that presenting and practicing the grammatical rules of a second language based on the order of the availability of the X-bar theory parameters positively affects the learners’ language proficiency.